2021
DOI: 10.1108/ijrdm-08-2020-0296
|View full text |Cite
|
Sign up to set email alerts
|

Framing the customer journey: touch point categories and decision-making process stages

Abstract: PurposeThis paper aims to define and frame the understanding of customer journeys, associated areas of consumer decision-making process stages and touch point categories based on an ownership perspective.Design/methodology/approachThe research is based on a detailed literature review of customer journeys, in peer-reviewed marketing and retail journals, within the last decade. The Chartered Association of Business Schools (ABS) academic journal guide marketing discipline list was used because it only includes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The increasing importance of CX to business performance, coupled with the emergence of the online retail environment, forces marketers to understand how to ensure a unique CX in the online environment (Rose et al, 2012). Towers and Towers (2022) also stated that there is a need to understand the customer journey and improve the CX throughout all the touchpoints. Even Kuppelwieser and Klaus (2020) indicated that customers evaluate and perceive the experience as a whole and do not perceive the different stages separately.…”
Section: The Case Of Footwear Online Stores 465mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing importance of CX to business performance, coupled with the emergence of the online retail environment, forces marketers to understand how to ensure a unique CX in the online environment (Rose et al, 2012). Towers and Towers (2022) also stated that there is a need to understand the customer journey and improve the CX throughout all the touchpoints. Even Kuppelwieser and Klaus (2020) indicated that customers evaluate and perceive the experience as a whole and do not perceive the different stages separately.…”
Section: The Case Of Footwear Online Stores 465mentioning
confidence: 99%
“…, 2012). Towers and Towers (2022) also stated that there is a need to understand the customer journey and improve the CX throughout all the touchpoints. Even Kuppelwieser and Klaus (2020) indicated that customers evaluate and perceive the experience as a whole and do not perceive the different stages separately.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In retailing, m-payment services represent touchpoints (Towers and Towers, 2022), where digital devices of customers and retailers are connected to enable transactions. Furthermore, IJRDM 51,3 NFC m-payment is an ecosystem of multiple actors (customers, mobile service providers, financial service companies, application developers and retailers).…”
Section: Theoretical Background 21 the Theory Of Technology Acceptanc...mentioning
confidence: 99%
“…To elaborate further on the consumer-packaging interaction, the current study relies on the customer journey literature, which shows how consumers move from one setting to another (Zomerdijk and Voss, 2010). Such studies take a business approach to characterise the journey of delivering an offering comprising a series of touch points and various delivery-related activities and events (Pantouvakis and Gerou, 2022;Towers and Towers, 2021;Zomerdijk and Voss, 2010), framing the journey as a process divided into the pre-purchase, purchase and Packaging journey from retail to home post-purchase stages (Lemon and Verhoef, 2016;Shavitt and Barnes, 2020). In accordance with the customer journey, the consumer-packaging interaction is a voyage that extends beyond the purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, the current study elaborates on the consumer–packaging interaction, based on the assumption that the interaction continues as the packaging moves from retail stores to consumers’ homes and even beyond. Relatedly, the study draws on the ideas of customer journey (Lemon and Verhoef, 2016; Shavitt and Barnes, 2020; Towers and Towers, 2021; Zomerdijk and Voss, 2010) and moments of consumption (Evans, 2019). It is thought that consumers likely infer different meanings from colour along the customer journey, as cues like colour impact responses in context (Kauppinen-Räisänen et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%